Optimized tri-band MIMO antenna design for 6G terahertz applications and future connectivity - Jamal Hossain Nirob; Kamal Hossain Nahin; Md. Ashraful Haque; Redwan A. Ananta; Narinderjit Singh Sawaran Singh; Md. Kawsar Ahmed; Md. Sharif Ahammed; Liton Chandra Paul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This paper presents an industrial and innovation rectangular-shaped multiple input multiple output (MIMO) antenna designed for terahertz (THz) frequency applications, specifically targeting 6G communication. The proposed antenna achieves triple-band operation at 3.62 THz, 6.248 THz, and 7.613 THz by incorporating four T-shaped slots. It is designed on a polyimide substrate with a dielectric constant of 3.5 and a tangent loss of 0.0027, with dimensions of 80 μm by 180 μm and a thickness of 11 μm. The patch and the ground plane are constructed from copper, ensuring robust performance. The antenna provides bandwidths of 0.7 THz, 2.2 THz, and 1.1 THz, with isolation levels exceeding -31.3 dB. It achieves a peak gain of 14.3 dB and a high efficiency of 94%, demonstrating its potential for high-performance THz applications. MIMO performance parameters, such as the envelope correlation coefficient (ECC), diversity gain (DG), mean effective gain (MEG), and total active reflection coefficient (TARC), exhibit excellent agreement with theoretical values. The design is further validated through simulations using computer simulation technology (CST) and a circuit model in advanced design system (ADS). The results of these tests mirrored those of the CST simulations, confirming the reliability of future 6G THz communication systems.